The ad-libitum taste test as measure of momentary alcohol use in the laboratory: an investigation of construct validity and confounding factors - Sebastian Trautmann; Anja Kräplin; Markus Muehlhan; Fée Ona Fuchs; Beate Loesch; Charlotte Wittgens (Psychopharmacology, 2024)
Rationale The ad-libitum taste test is a widely used covert measure of motivation to consume alcohol in the laboratory. However, studies on its construct validity and potential confounding factors are scarce. Objectives This study aimed to evaluate the construct validity of the ad-libitum taste test by examining the association of ad-libitum alcohol consumption with typical alcohol use and craving, and investigating potential moderation by trait anxiety, depressiveness, current mood, and drinking motives. Methods A sample of 264 young male individuals were offered two 0.33 l glasses of beer. Participants were instructed to rate the characteristics of each drink, while the percentage of beverages containing alcohol consumed was assessed. Associations of ad-libitum consumption with typical alcohol use and craving were assessed using non-parametric and piecewise regressions. Moreover, moderator analysis with trait anxiety, depressiveness, current mood, and drinking motives was carried out. Results Ad-libitum alcohol consumption was associated with typical alcohol use and alcohol craving. However, these associations decreased at high consumption levels. Associations between ad-libitum consumption, typical alcohol use, and craving were stable across several conditions, except that the association between ad-libitum consumption and craving increased with higher social, conformity, and coping drinking motives. Conclusions The ad-libitum taste test appears to be a valid measure of the motivation to drink alcohol in laboratory studies in young male adults, although this validity might be compromised at high levels of ad-libitum consumption. Consideration of these factors can contribute to further refining the ad-libitum taste test as a valuable tool for assessing motivation to consume alcohol in laboratory studies.

The role of childhood trauma and stress reactivity for increased alcohol craving after induced psychological trauma: an experimental analogue study - Sebastian Trautmann; Anja Kräplin; Raoul Dieterich; Jan Richter; Markus Muehlhan (Psychopharmacology, 2018)